(untitled) (Asian Business Research, 2018)
Till date numerous theories in the field of marking has recognized both the need for improved marketing skills and the literature which provide in-depth analysis and details about such marketing skills and competencies for the help of marketing managers. For the current work, a questionnaire was served over the managers of 162 companies, constituting 52 percent of industrial firms in Abu Dhabi. A pre-tested questionnaire having details about three prominent dimensions of leadership management, marketing and personal attributes, as measures of company performance were sent to them to analyse and to add to existing stock of knowledge on marketing skills and competency. The questionnaire turnover ratio was 77 percent, which was suitable for statistically significant analysis. The current research has been carried out with aim to find out how much fund multi-national companies (MNCs) should allocate to Human Resource building, also to bring out competencies issues across industries, along with that to develop nexus between employee competencies and firm performance and finally to devise an appropriate mechanisms through which these relationship in companies may operate. Findings of the current work revealed that human resource competencies on the firm performance from marketing perspectives paly its role through different channels namely organizational cultural, communication system, managing changes, knowledge sharing, employees inspiration by leaders, global completion, empowering employees, leadership competency and taking initiatives by employees. It has been observed that performance perception, which is based on manager individual perception and a managerial style, has a negative impact on perceived benefits of creativity negligence factors. Out of nine motivating factors, only five factors were found having statistically significant impact on the competencies of firms in the selected sample of manufacturing and service industries. Analysis shows that management initiatives highlight the fact that not all of them are necessarily successful.